Pembuatan Booklet Mitigasi Bencana Gempa Bumi dan Tsunami Sebagai Media Informasi bagi Masyarakat Kota Padang - Agusti, Diana; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis research was aimed to make booklet mitigation for an earthquake and tsunami disaster as information media of Padang Society. This paper pupose to description creation phase booklet mitigation for an earthquake and tsunami disaster. The research method used in this paper is a descriptive method. Data resources was obtained from interview, electronic media, and non electronic media. For creating process booklet mitigation for an earthquake and tsunami disaster as information media, first step prepare tools and materials, tools and materials used in this making phase is computer or laptop connected to the internet network, printer and Canva software. The other materials that also we need is booklet art paper. Second, follow the steps according to the booklet making methodology: a) Determine the title an sub title booklet; b) Format making or booklet structure,; c) Searching for information that need as booklet content; d) Processing information; e) Arrenge and place information according to the booklet format; f) Creating booklet design and editing using Canva application; g) Printing booklet. Third, constraints and efforts in the process of making booklets. Constraints faced are an unstable internet connection that causes the editing process using the canva application cannot be run. The effort is to find a place with a stable internet connection.Â Keywords: booklet, mitigation disaster, earthquake,Â tsunami